Economic Evaluation of Supplying Commercial Thermal Load by ‎a New CPVT System: A Case Study in Iran - Amir Abedanzadeh; Hasti Borgheipour; Samaneh Fakouriyan; Farschad Torabi (Journal of Applied and Computational Mechanics, 2023)
This paper aims to provide a concentrated photovoltaic thermal (CPVT) system regarding the high potential of receiving solar energy in Iran. Generated thermal energy of the system supplies the average thermal load of a commercial building and also its generated electricity is sold to the grid according to Iran's feed-in tariff (FiT). In order to calculate the system profitability, an economic evaluation is done in 20 years that is regarded as a novel approach. Furthermore, sensitivity analyses are performed to develop the results to the other locations with different economic conditions and various potential of energy resources, and also to present an appropriate financial outlook. The results demonstrate that the system is highly profitable given net present value (NPV) of 551.55 k$, internal rate of return (IRR) of 150.79%, benefit to cost ratio (BCR) of 10.32, payback time (PBT) of 0.51 years, and levelized cost of energy (LCOE) of 0.1293 $/MWh. Moreover, sensitivity analyses show that the system profitability is greatly appropriate even regarding the variety of unpredictable parameters. For instance, if the generated energy decreases by 20%, IRR and PBT will equal 120.63% and 0.63 years respectively, and the system can still maintain its high profitability. Moreover, it has been revealed that the enhancement of FiT can increase the system's economic efficiency. According to the results, it is noticeably profitable to use the CPVT systems to produce electrical and thermal power in countries with a high potential of receiving solar energy (especially middle-eastern countries).